Proteomics methods to study methionine oxidation. Issue 2 (31st October 2013) - Ghesquière, Bart; Gevaert, Kris; Allan Butterfield, D.; Dalle‐Donne, Isabella
Abstract The oxidation and consequent reduction of protein‐bound methionine residues is of great interest in understanding different aspects of how oxidative stress affects protein functions and cellular signaling. To date, few technologies are available for the study of methionine sulfoxides. And, especially the absence of highly specific antibodies has impeded the field in understanding the exact role of methionine oxidation on a proteome‐wide level. Nonetheless, the different models where the responsible enzymes for repair of the oxidized methionines have been studied show that there is an important role for this modification in a cellular context. We here review different mass spectrometry based and proteomics methods for characterizing in vivo methionine oxidation. © 2013 Wiley Periodicals, Inc. Mass Spec Rev 33: 147–156, 2014.